2006
DOI: 10.1175/jcli3605.1
|View full text |Cite
|
Sign up to set email alerts
|

A Simulated Climatology of Asian Dust Aerosol and Its Trans-Pacific Transport. Part I: Mean Climate and Validation

Abstract: The Northern Aerosol Regional Climate Model (NARCM) was used to construct a 44-yr climatology of spring Asian dust aerosol emission, column loading, deposition, trans-Pacific transport routes, and budgets during 1960-2003. Comparisons with available ground dust observations and Total Ozone Mapping Spectrometer (TOMS) Aerosol Index (AI) measurements verified that NARCM captured most of the climatological characteristics of the spatial and temporal distributions, as well as the interannual and daily variations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
113
1
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(129 citation statements)
references
References 48 publications
(54 reference statements)
12
113
1
3
Order By: Relevance
“…This situation is favorable to suppress deposition of the dust aerosols and to lead a high concentration condition, and consequently Asian dust is easily recognized. The process is supported by the results of numerical experiments (Wang and Fang 2006;Zhao et al 2006). Wang and Fang (2006) reveals that ascending motion existed in the warm sector, which lifted dust up to 300 hPa.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 58%
See 1 more Smart Citation
“…This situation is favorable to suppress deposition of the dust aerosols and to lead a high concentration condition, and consequently Asian dust is easily recognized. The process is supported by the results of numerical experiments (Wang and Fang 2006;Zhao et al 2006). Wang and Fang (2006) reveals that ascending motion existed in the warm sector, which lifted dust up to 300 hPa.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 58%
“…Concentration of dust aerosols decrease gradually as the distance from the source regions increases due to diffusion and gravitational removal (dry and wet deposition). Actually, observational (e.g., Sun et al 2001) and modeling (e.g., Zhao et al 2006) studies indicated that maximum of dust deposition was found over the dust source and nearby regions with most of the emitted dust redeposited onto the dust source areas. Asian dust observed manually and it can not be recognized when the concentration is too low.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…8). The highest dust fluxes of ∼2-4 g/m 2 /yr are observed west of ∼165 • E and south of ∼45 • N in the southwestern part of the INOPEX cruise track, along the middle of the main pathway of the westerly jet transporting dust over the North Pacific (Husar et al, 2001;Uematsu et al, 2003;Weber et al, 1996;Yumimoto et al, 2009;Zhao et al, 2006). To the north and east of this region, dust fluxes gradually decrease to ∼1-2 g/m 2 /yr over the remainder of the SNP.…”
Section: Spatial Dust Flux Pattern In the Subarctic North Pacificmentioning
confidence: 94%
“…It is the second largest shifting sand desert in the world, with about 85% of shifting sand dunes (Sun and Liu, 2006).As an area where sandstorms occur frequently, it is known as an important sand-dust source in China (Wang et al, 2000;Qian et al, 2002;Zhou et al, 2002).Sandstorms caused by soil wind erosion in this region have produced great effects on the climatic change in East Asia (Zhao et al, 2006). The Tazhong was regarded as for the saltation activity observation experiment.…”
Section: Study Areamentioning
confidence: 99%